Pengaruh Struktur Modal dan Profitabilitas terhadap Nilai Perusahaan dengan Ukuran Perusahaan sebagai Variabel Moderasi - Rachmadevi, Gita Astika; Purwohedi, Unggul; Ulupui, I Gusti Ketut Agung (Jurnal Akuntansi, Perpajakan dan Auditing, 2023)
The purpose of this study is to test and analyze the effect of capital structure and profitability on company value with company size as moderating variable. This study used secondary data from financial report in the mining sector and basic industry and chemicals sector in 2019-2021 using a purposive sampling method. Based on the criteria, the sample used for this study was 48 companies in the mining sector and 68 companies in the basic industry and chemicals sector. The analysis technique used is panel data regression analysis using software EViews. The results showed that capital structure has a positive effect on the company value, profitability has a negative effect on the company value, company size has a negative effect on the company value, company size is able to moderate the effect of capital structure on company value, and company size is able to moderate the effect of profitability on company value.